Seizures with tonic posturing: Semiologic difference between supplementary sensorimotor area (SSMA) origin and extra‐SSMA origin. (13th December 2015) - Sitthinamsuwan, Bunpot; Usui, Naotaka; Tottori, Takayasu; Terada, Kiyohito; Kondo, Akihiko; Matsuda, Kazumi; Baba, Koichi; Inoue, Yushi
Summary: In seizures with tonic posturing, differentiation of seizures originating in SSMA from seizures originating in cortices other than SSMA and spreading to SSMA has not been previously attempted. Twenty‐two patients were studied with intractable focal epilepsy with tonic limb posturing as the most prominent semiology, who underwent resective surgery and obtained favorable postoperative seizure outcomes. These 22 patients were divided into an SSMA group (N = 12) and an extra‐SSMA group (N = 10), according to the location of resection. Resection area in the extra‐SSMA group was located in the dorsolateral frontal or prefrontal area in four patients, the frontal operculum (insula) in two, the parietal cortex in three, and the temporoparietal cortex in one patient. Video‐recorded seizures were carefully reviewed. Tonic posturing characteristics and the presence or absence of accompanying symptoms were compared between groups. Incidence of preservation of consciousness was significantly higher in the SSMA group (p < 0.001). Patients in the SSMA group demonstrated a propensity for having unilateral or bilateral asymmetrical tonic limb posturing. In contrast, patients in the extra‐SSMA group had a statistically significantly higher incidence of bilateral symmetrical tonic limb posturing (p < 0.05). These findings may be helpful in identifying seizure origin.